Popliteal artery injury during posterior cruciate ligament reconstruction - Marcos Henrique Frauendorf Cenni; Bruno Fajardo do Nascimento; Guilherme Galvão Barreto Carneiro; Rodrigo Cristiano de Andrade; Lúcio Flávio Biondi Pinheiro Júnior; Oscar Pinheiro Nicolai (Revista Brasileira de Ortopedia, 2015)
This study reports a case of popliteal artery injury during arthroscopic reconstruction of the posterior cruciate ligament. The evolution of the injury is described and comments are made regarding the anatomy of this artery and potential risks of this surgical technique. This study had the aims of alerting the medical community, especially knee surgeons, regarding a severe surgical complication and discussing the ways of preventing it.